173 Immunosuppressant discontinuation in systemic lupus erythematosus: prevalence, risk of subsequent flare and effect on damage accrual. (April 2019) - Zen, Margherita; Saccon, Francesca; Larosa, Maddalena; Gatto, Mariele; Iaccarino, Luca; Doria, Andrea
Abstract : Background: Patients with Systemic Lupus Erythematosus (SLE) are often exposed to prolonged treatment with immunosuppressants (IS). Remission of disease activity should conceptually enable IS withdrawal, but no enough evidence is available regarding the benefits of IS discontinuation, especially in non-renal SLE, or the risk of a subsequent flare. Our aims were to assess the rate of IS withdrawal in SLE remitted patients and the predictors of a subsequent flare and flare-free survival; moreover, to evaluate the effect of IS withdrawal on damage accrual. Methods: We studied patients diagnosed with SLE between 1990 and 2018 treated with IS over their disease course who discontinued ISs. IS discontinuation was defined as complete withdrawal of any IS. Reasons for discontinuation were: remission, defined as clinical SLE Disease Activity Index (SLEDAI)−2K=0, or poor compliance/intolerance. Flares were defined according to SLEDAI Flare Index. Predictors of a subsequent flare and flare-free survival were analyzed by multivariate logistic regression and Cox regression analysis, respectively. Results: Eligible patients ever treated with IS were 319 out of 456. 139 patients discontinued ISs, 105 of them (75.5%) due to remission. Mean ±SD follow-up after IS withdrawal was 91±71 months (range 6–372). 26/105 remitted (24.7%) and 23/34 unremitted patients (67.6%) experienced a flare (p<0.001), a median (range) of 57 (6–264) and 8 months (1–72) after IS discontinuation, respectively (p=0.009). Flare-free survival is depicted in figure 1 . Table 1 reports characteristics of remitted patients, overall and according to flare occurrence after IS discontinuation. At multivariate logistic regression analysis, antimalarial intake (OR, 95% CI 0.103, 0.023–0.452, p=0.003), older age (OR 0.943, 0.892–0.997, p=0.039) and the duration of remission before IS discontinuation (OR 0.943, 0.938–0.996, p=0.025) were independent protective factors against flares after IS discontinuation. Conversely, no predictive factors of a longer time-to-flare were identified by multivariate Cox-regression analysis. Median damage accrual was similar in patients who discontinued (1, range 0–8) or not IS (1, range 0–9) after adjusting for age, disease duration and cumulative prednisone dose. We separately analyzed data of non-renal remitted patients (37 patients, 35.2%). The only variable associated with a lower flare rate was antimalarial intake (OR 0.048, 0.005–0.503, p=0.002). Conclusions: In our cohort, one third of patients treated with IS discontinued the drug during the follow-up, in most cases due to remission. The use of antimalarials after IS discontinuation was independently associated with a significant decrease in the risk of flare. Funding Source(s): None Table 1 reports characteristics of remitted patients, overall and according to flare occurrence after IS discontinuation.